Menumbuhkan Kepedulian Sosial melalui Kegiatan Pembagian Sembako dan Pakaian Layak Pakai kepada Masyarakat Sekitar - Mila Hariani; Adira Devina Mahmudi; Rahayu Mardikaningsih; Didit Darmawan; Arif Rachman Putra (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The ongoing social and economic disparities in society mean that some groups experience limitations in meeting basic needs, particularly food and clothing. This situation necessitates the involvement of various parties, including students, in social activities as a form of community service. This community service activity aims to assist underprivileged communities by distributing basic necessities and suitable clothing and fostering empathy, social awareness, and responsibility in students towards their surroundings. The method used was Participatory Action Research (PAR), which emphasizes the active participation of students, lecturers, and the community at every stage of the activity. The activity was carried out on December 20, 2025, in the area around Sunan Giri University, Surabaya, with third-semester scholarship students as implementers. The results of the activity showed that the program received a positive response from the beneficiary community and strengthened relationships between students and the community. This activity also increased social awareness, empathy, and a spirit of mutual cooperation among participants. Thus, the distribution of basic necessities and suitable clothing is an effective form of community service in strengthening social solidarity and concern for groups in need.